Pengaruh Efikasi Diri Dan Kompetensi Intelektual Terhadap Kinerja Guru Dengan Dukungan Organisasi Sebagai Pemoderasi (Studi pada Yayasan Pendidikan Nurul Falah Kemuning Kecamatan Tunjung Teja) - Wicaksono, Arief; Lutfi, Lutfi (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2022)
The efficacy and intellectual competence of teachers are very important for an educational institution, where it will participate in determining the results of the education made by the institution or school. The purpose of this study was to examine and analyze the effect of self-efficacy and intellectual competence on teacher performance with organizational support as moderating. The research method used. The approach used in this study is a quantitative approach, the sampling population is 34 people, the data analysis technique used is the PLS SEM method. The results showed self-efficacy has a positive and significant effect on the performance of teachers who are accepted; intellectual competence has a positive and significant effect on teacher performance, so the accepted hypothesis is that the direction of the influence is negative, organizational support has a positive and significant effect on teacher performance, the direction of the negative influence is rejected; organizational support memorization of the relationship between self-efficacy on teacher performance does not strengthen the relationship between self-efficacy, organizational support moderates the relationship between intellectual competence on teacher performance does not strengthen the relationship between intellectual competence and teacher performance